Effects of Level 3 Automated Vehicle Drivers’ Fatigue on Their Take-Over Behaviour: A Literature Review - Hanying Guo; Yuhao Zhang; Shanshan Cai; Xin Chen (Journal of Advanced Transportation)
With advancements in automated driving technology, Level 3 vehicle automation has been proliferating. In Level 3, drivers can turn their attention to things unrelated to driving and only takeover in cases of emergency. However, the transition to the main driving task can be affected by different physical and psychological changes in drivers such as fatigue and distraction. Although existing research in the field of manual driving has demonstrated the effects of fatigue on driver performance, there have been relatively few studies on fatigue in the field of automated driving. Fatigue decreases drivers’ alertness, which can prevent drivers from conducting necessary emergency takeover manoeuvres in a safe and timely manner. This systematic literature review was conducted to establish relationships between driving fatigue and takeover behaviour in the existing literature on Level 3 automated driving systems. Different from existing reviews of driving fatigue, this paper focuses on the commonly used and most effective evaluation indicators of driving fatigue and further discusses the methods to improve the takeover efficiency of fatigued drivers. This is the first detailed systematic review of general relationships between fatigue in automated driving and drivers’ takeover behaviours when the vehicle sends a takeover request. Researchers are invited to expand on the findings here to further clarify the findings on the associations between driver fatigue indicators in automated vehicle driving and drivers’ takeover response times.